Coagulation status in patients with pulmonary embolism receiving long-term anticoagulant therapy - E. A. Shmidt; S. A. Berns; T. Yu. Penskaya; I. I. Zhidkova; O. V. Gruzdeva; O. L. Barbarash (Кардиоваскулярная терапия и профилактика)
Aim. To study the blood coagulation status by various laboratory methods in patients after pulmonary embolism (PE) receiving long-term anticoagulant therapy.Material and methods. The blood of 23 patients with pulmonary embolism, who received long-term anticoagulant therapy, was studied. The study of coagulation profile, D-dimer, thrombodynamics, thromboelastography and thrombin generation test were carried out.Results. The thrombin generation test shows a significant increase in the time of its formation, while the maximum amount of thrombin formed is half that of the reference values. There is a slightly increased median fibrin clot growth rate in the thrombodynamics test — 30,4 gm/min with a normal coagulation rate of 20-29 gm/min. The result of thromboelastography also reflects the blood hypocoagulation, in terms of R, Angle a and CI.Conclusion. Integral methods for assessing the thrombotic readiness in combination with a routine coagulation panel demonstrate a complete picture of blood coagulation potential in patients after pulmonary embolism requiring long-term anticoagulant therapy.